2014
DOI: 10.1007/s00404-014-3560-6
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery impedance during puerperium in normotensive and chronic hypertensive pregnant women

Abstract: Chronic stage-1 hypertensive women with normal pregnancy outcomes exhibited a progressively increasing postpartum UtA impedance. This trend also occurred in normotensive women, albeit at a significantly lower magnitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
3
5
0
3
Order By: Relevance
“…Tekay and Jouppila and Jaffa et al reported a PI of 1.19 and 1.20, respectively. Nevertheless, our findings were consistent with our previous results and fell within the normal range described by Guedes‐Martins et al…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Tekay and Jouppila and Jaffa et al reported a PI of 1.19 and 1.20, respectively. Nevertheless, our findings were consistent with our previous results and fell within the normal range described by Guedes‐Martins et al…”
Section: Discussionsupporting
confidence: 94%
“…Nevertheless, they started Doppler measurements on the third postpartum day, thus lacking the immediate postpartum changes, and there was no control group. Guedes‐Martins et al have investigated the effect of HTN on the UtA in the puerperium period, in patients with CS but not with VD. They also investigated UtA flow during the postpartum period and reported that UtA flow impedance increases as puerperium progresses .…”
Section: Discussionmentioning
confidence: 99%
“…But the difference for presence of early diastolic notch between the two groups of cases was disappeared in the late postpartum periods, mainly because of the increasing frequency of early diastolic notch in postpartum period in group 2 (normal pregnancy). The finding that the proportion of cases with early diastolic notch was increasing in normal pregnancy is consistent to the findings of other reports [3338]. This trend may be based on a process for uterine artery to return to the non-pregnant state.…”
Section: Discussionsupporting
confidence: 91%
“…This means that the mean value of uterine artery PI was around the upper cut-off values of normal range. Another study also reported the mean values of UtA PI within normal range even in hypertensive group [33]. …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation